A quadratic identity in the shuffle algebra and an alternative proof for de Bruijn's formula. (January 2022) - Colmenarejo, Laura; Diehl, Joscha; Sorea, Miruna-Ştefana
Abstract: Motivated by a polynomial identity of certain iterated integrals, first observed in Colmenarejo et al. (2020) in the setting of lattice paths, we prove an intriguing combinatorial identity in the shuffle algebra. It has a close connection to de Bruijn's formula when interpreted in the framework of signatures of paths.